2020
DOI: 10.1002/gcc.22895
|View full text |Cite
|
Sign up to set email alerts
|

Poorly differentiated chordoma with whole‐genome doubling evolving from a SMARCB1‐deficient conventional chordoma: A case report

Abstract: Evolution of poorly differentiated chordoma from conventional chordoma has not been previously reported. We encountered a case of a poorly differentiated chordoma with evidence of whole-genome doubling arising from a SMARCB1-deficient conventional chordoma. The tumor presented as a destructive sacral mass in a 43-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In our case number 6 with both conventional and poorly differentiated chordoma components, we found heterozygous deletion of SMARCB1 in the conventional chordoma component without additional genetic alterations. Similar to our previous case report of axial poorly differentiated chordoma, 39 the extra‐axial poorly differentiated chordomas (two cases) demonstrated a complex hyperdiploid genomic profile with gain of multiple chromosomes and a homozygous deletion of SMARCB1 . No mutations or structural variants were identified in all three extra‐axial chordomas with available NGS‐targeted sequencing analysis (MSK‐IMPACT).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our case number 6 with both conventional and poorly differentiated chordoma components, we found heterozygous deletion of SMARCB1 in the conventional chordoma component without additional genetic alterations. Similar to our previous case report of axial poorly differentiated chordoma, 39 the extra‐axial poorly differentiated chordomas (two cases) demonstrated a complex hyperdiploid genomic profile with gain of multiple chromosomes and a homozygous deletion of SMARCB1 . No mutations or structural variants were identified in all three extra‐axial chordomas with available NGS‐targeted sequencing analysis (MSK‐IMPACT).…”
Section: Discussionsupporting
confidence: 87%
“…Poorly differentiated variant of chordoma is a tumor of pediatric and young adult age group, commonly occurring at clivus/cervical vertebral location and is pathologically characterized by sheets of epithelioid cells with eosinophilic cytoplasm, nuclear atypia and loss of INI‐1 expression due to inactivating mutations and/or recurrent isolated copy number losses involving SMARCB1 at 22q11.23 5–7 . In a prior case report of a conventional chordoma from the sacrum with transformation to poorly differentiated chordoma, we showed that SMARCB1 loss (homozygous) may be an early event in rare cases of axial conventional chordoma and a poorly differentiated chordoma can evolve through additional genomic aberrations such as doubling of the genome 39 . Extra‐axial poorly differentiated chordoma is exceptionally rare with a single published case report of a 67‐year‐old female who presented with a knee mass with destruction of the medial cortex of metadiaphysis of distal femur and a large extraosseous soft tissue mass 21 …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The PDC, a tumor that often occurs in children, prefers the base of the skull and appears nuclear TBXT positivity along with INI-1 loss [ 34 , 35 ]. Case analysis findings suggest that a SMARCB1 deletion is an early event in the rare traditional chordoma that may transform into PDC through supernumerary genome variation [ 36 ]. SMARCB1/INI1-negative PDC is a unique subset of chordomas with clinical, histopathological, and molecular specificity, rapid progression, and poor prognosis, and should not be confused with traditional chordomas [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brachyury is a transcription factor in the T-box group and is highly specific for chordoma 19,20 ; it is diffusely positive in this condition. [21][22][23] Poorly differentiated chordoma (PC) also shows diffuse positivity for brachyury, [24][25][26] with complete loss of 24 One extra-axial PC case has been described, but showed diffuse positivity for brachyury, 27 in contrast to METC. In addition, PC shows mild to moderate nuclear pleomorphism, abundant eosinophilic cytoplasm, and geographical necrosis.…”
Section: Discussionmentioning
confidence: 99%